Reduction of Methicillin-Resistant Staphylococcus aureus (MRSA) Infection in Long Term Care is Possible While Maintaining Patient Socialization: A Prospective Randomized Clinical Trial - Peterson, Lance R. (Am J Infect Control, 2016)
BACKGROUND: Antibiotic resistance is a challenge in Long Term Care Facilities (LTCFs). The objective was to demonstrate that a novel, minimally invasive program not interfering with activities of daily living (ADL) or socialization could lower methicillin-resistant Staphylococcus aureus (MRSA) disease. METHODS: This was a prospective, cluster-randomized, non-blinded trial initiated at three LTCFs. During Year 1 units were stratified by type of care and randomized to intervention or control. In Year 2 all units were converted to intervention consisting of universal decolonization using intranasal mupirocin and a chlorhexidine bath performed twice (two decolonization/bathing cycles one month apart) at the start of the intervention period. Subsequently, after initial decolonization, all admissions were screened on site using real-time PCR and those MRSA positive were decolonized, but not isolated. Units received annual instruction on hand hygiene. Enhanced bleach wipe cleaning of flat surfaces was done every four months. RESULTS: 16,773 tests were performed. The MRSA infection rate decreased 65% between the baseline (44 infections during 365,809 patient-days) and Year 2 (12 during 287,847 patient-days; p<0.001); significant reduction was observed at each of the LTCFs (p<0.03). DISCUSSION AND CONCLUSION: On-site MRSA surveillance with targeted decolonization resulted in a significant decrease in clinical MRSA infection among LTCF residents.